Structural magnetic resonance imaging findings and histopathological correlations in motor neuron diseases—A systematic review and meta-analysis - Zejlon, Charlotte; Nakhostin, Dominik; Winklhofer, Sebastian; Pangalu, Athina; Kulcsar, Zsolt; Lewandowski, Sebastian; Finnsson, Johannes; Piehl, Fredrik; Ingre, Caroline; Granberg, Tobias; Ineichen, Benjamin Victor (Frontiers in Neurology, 2022)
Objectives: The lack of systematic evidence on neuroimaging findings in motor neuron diseases (MND) hampers the diagnostic utility of magnetic resonance imaging (MRI). Thus, we aimed at performing a systematic review and meta-analysis of MRI features in MND including their histopathological correlation. Methods: In a comprehensive literature search, out of 5941 unique publications, 223 records assessing brain and spinal cord MRI findings in MND were eligible for a qualitative synthesis. 21 records were included in a random effect model meta-analysis. Results: Our meta-analysis shows that both T2-hyperintensities along the corticospinal tracts (CST) and motor cortex T2*-hypointensitites, also called “motor band sign”, are more prevalent in ALS patients compared to controls (OR 2.21 [95%-CI: 1.40-3.49] and 10.85 [95%-CI: 3.74-31.44], respectively). These two imaging findings correlate to focal axonal degeneration/myelin pallor or glial iron deposition on histopathology, respectively. Additionally, certain clinical MND phenotypes such as amyotrophic lateral sclerosis (ALS) seem to present with distinct CNS atrophy patterns. Conclusions: Although CST T2-hyperintensities and the “motor band sign” are non-specific imaging features, they can be leveraged for diagnostic workup of suspected MND cases, together with certain brain atrophy patterns. Collectively, this study provides high-grade evidence for the usefulness of MRI in the diagnostic workup of suspected MND cases. Trial registration number: CRD42020182682